The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1007/bf02458528
|View full text |Cite
|
Sign up to set email alerts
|

Time dependencies of Bradford distributions: Structures of journal output in 20th-century logic and 19th-century mathematics

Abstract: Time dependencies of Bradford distributions are investigated for 19th-century mathematics and for 20th-century logic. To facilitate comparisons, for the representation of empirical Bradford distributions "Pareto's law" and Lorenz diagrams are used. It is shown that the character of a Bradford distribution (including the "core zone" and the "Groos droop") depends on the stage in the development of a scientific field and that it varies with the time-span considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…A few scientometric studies are available for the philosophy of science [GEISLER, 2005] and mathematical logic [WAGNER-DÖBLER, 1997], the latter of which is the core in the philosophy of science. But they are not for the definition of science.…”
Section: Methods Of Definitionmentioning
confidence: 99%
“…A few scientometric studies are available for the philosophy of science [GEISLER, 2005] and mathematical logic [WAGNER-DÖBLER, 1997], the latter of which is the core in the philosophy of science. But they are not for the definition of science.…”
Section: Methods Of Definitionmentioning
confidence: 99%
“…Recently, Wagner‐Döbler (1997) has shown that there are qualitative differences between the distributions of publications in journals over time. We applied the Mann‐Whitney test to the Mathematical Logic successive decades in Table 1.…”
Section: Applying the Test To Publications In Journalsmentioning
confidence: 99%
“…There are numerous of examples of applications of Bradford law in various disciplines like natural sciences and social sciences (e.g. Wagner-Döbler, 1997;Peritz, 1990). This law seems to be a very robust and commonly appearing phenomenon in most of the current literature databases and bibliographies.…”
Section: Introductionmentioning
confidence: 99%